Ethanobotanical studies on Achyranthes aspera Linn. among the folk peoples of Tamilnadu, South India - Veluchamy Balakrishnan, Kaliappan Kamalakannan (Journal of Phytology, 2009)
The study documents indigenous Achyranthes aspera used for folk and tribal medicine in South Indian medicinal system.We have to take the survey among the village peoples and tribal peoples in concern district of Tamilnadu .The plant are commonly used for certain diseases and this is discussed with the literature.